Penerapan Smart Trash Monitoring System untuk Memantau Sampah Rumah Tangga di Perumahan Graha Panyindangan Estate Indramayu - Fauzan Ishlakhuddin; Esti Mulyani; Eka Ismantohadi (Lembaga Pengembangan Kinerja Dosen, 2025)
Household waste management is a significant challenge in creating clean, healthy, and sustainable residential areas. Dependence on manual monitoring methods often leads to delays in waste collection, waste pile-ups, and operational inefficiencies. This community service program implements a Smart Trash Monitoring Sistem (STMS) based on the Internet of Things (IoT) in Graha Panyindangan Estate, Indramayu. The system utilizes ultrasonic sensors and ESP32 to detect waste levels and sends real-time data to a dashboard accessible by residents and cleaning staff. The results of implementing STMS show improved efficiency in waste management, with waste collection being carried out on time based on accurate, real-time data. This system also reduces the need for manual inspections and encourages responsible waste management behavior among residents. In addition to technical benefits, there have been social changes, such as increased environmental awareness and the formation of new social norms within the community. The involvement of local leaders in supporting the system’s sustainability further strengthens the implementation of the smart living concept, resulting in a cleaner, healthier, and more sustainable residential environment in the long term.